Determining the vitamin D supplementation duration to reach an adequate or optimal vitamin D status and its effect on blood lipid profiles: a longitudinal study - Sakineh Nouri Saeidlou; Davoud Vahabzadeh; Fozieh Karimi; Fariba Babaei (BMC, 2024)
Abstract Background Recently, Serum vitamin D (Vit. D) levels evaluation and the use of Vit. D supplements have increased substantially. There is no specific guideline for the duration of Vit. D supplementation, so yet Vit. D supplementation duration has remained a critical and controversial issue. This study aimed to determine the vit. D supplementation duration to reach an adequate or optimal Vit. D status and its effect on lipid profile. Methods In this longitudinal study, 345 women with different status of Vit. D levels were enrolled and followed up for one year. Eligible participants received 50,000 IU Vit. D3 (cholecalciferol) once a month for 12 consecutive months. The serum Vit. D levels and lipid profiles were measured at baseline, 3rd, 6th, and 12th months after the intervention. Participants were categorized based on Vit. D level at baseline into deficiency (< 20 ng/mL), inadequate (20-30 ng/mL), and adequate (> 30 ng/mL) groups, and the data were compared at different times between the three groups. Results Three deficiency (n = 73), inadequate (n = 138) and adequate (n = 134) groups of participants were followed. In all participants the average amount of Vit. D level changes were 8 ng/mL after one year of supplementation. The mean changes of serum Vit. D level in 6th and 12th months vs. 3th month was as below: In deficiency group: 4.08 ± 0.85 and 10.01 ± 1.02 ng/mL; (p < 0.001), in inadequate group: 3.07 ± 0.59 and 7.26 ± 0.78 ng/mL; (p = 0.001) and in adequate group: 2.02 ± 0.88 and 6.44 ± 1.005 ng/ml; (p = 0.001). Lipid profiles were improved in three groups. So, the mean changes of lipid profiles at the end of the study comparing with the baseline were: -5.86 ± 2.09, -7.22 ± 1.43 and − 6.17 ± 1.72 (mg/dl) for LDL (p < 0.05); -12.24 ± 3.08, -13.64 ± 3.21 and − 17.81 ± 2.94 (mg/dl) for cholesterol (p < 0.05) in deficiency, inadequate and adequate groups, respectively. For triglyceride, the mean changes were − 13.24 ± 5.78 and − 15.85 ± 7.49 (mg/dl) in deficiency and adequate groups, respectively (p < 0.05). Although the triglyceride decreased in the inadequate group at the end of the study but this difference was not significant (p = 0.67). Conclusion Taking of 50,000 IU Vit. D 3 monthly for 12 months resulted in reaching its level to adequate level in both deficiency and insufficient groups; however, in the adequate group its level did not reach above than 50 ng/mL. Therefore, 50,000 IU Vit. D3 supplementation monthly for one year can have beneficial effects on lipid profiles and there is no risk of toxicity in healthy women.